STRATEGI SATUAN POLISI PAMONG PRAJA DALAM PENYELENGGARAAN KETENTRAMAN, KETERTIBAN UMUM DAN PERLINDUNGAN MASYARAKAT - Sopandi, Andi; Mulyana, R. Achmad (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2024)
The strategy of the Bekasi City Civil Service Police Unit in implementing peace, public order, andcommunity protection in Bekasi City requires a comprehensive study. The purpose of this paper is toanalyze the strategies carried out by the Bekasi City Civil Service Police Unit in the implementation of peace, public order, and community protection. The research uses a qualitative approach with datacollection techniques through interviews and focused discussions. The data analysis technique uses thetriangulation technique. The results obtained show that there are: (a) an inventory of public order andtranquility conditions in Bekasi City; (b) Efforts to monitor and evaluate vulnerable points that maydisturb public order and tranquility; and (c) strategies and prevent and take action against every casethat disturbs public order and tranquility.